Surviving the Global Financial Crisis : Foreign Ownership and Establishment Performance - Alfaro, Laura; Chen, Maggie Xiaoyang (2012)
This paper examines how different establishments performed during the recent global financial crisis, focusing on the role of foreign ownership. The paper investigates how foreign ownership affected establishments' responses to negative economic shocks, using a cross-country panel dataset with detailed information on operation, location and industry for more than 12 million establishments from 2005-2008. The evidence shows that multinational subsidiaries on average fared better than local counterfactuals with similar economic characteristics. Among multinational subsidiaries, establishments with stronger production and financial linkages with parent companies showed greater resilience. Finally, in contrast to the crisis period, the impact of foreign ownership and linkages on an establishment's performance was insignificant in non-crisis years.